The THE EFFECT OF ACUPRESSURE AT SP 6 POINT ON LABOR PAIN IN THE 1ST STAGE OF THE ACTIVE PHASE - Nurmanisa, Nazma (Jurnal Kesehatan Siliwangi, 2024)
Childbirth is a physiological thing that everyone experiences. The 2017 Indonesian Demographic and Health Survey (SDKI) report shows that 17% of live births in the 5 years prior to the survey were from women 15-49 years old who were born via caesarean section. Fear is the main factor that causes pain in labor. Labor pain is one of the most intense types of pain that a woman may experience. Pain in women giving birth is normal because it is influenced by anatomical and physiological factors in the body. Controlling delivery pain is very important in order to progress the delivery process. One way is to use non-pharmacological techniques, namely the accupressure technique. The aim is to determine the effectiveness of applying acupressure to the SP 6 point to reduce pain in women giving birth. This research method uses article searches with the e-databased search engines Pubmed, and Google Scholar for 2013-2023 with the criteria of original articles, RCT, Systematic Review, and experimental methods. From the search results, 1 article was obtained that met the criteria.  Applying pressure at the SP6 point can reduce the labor pain felt by the mother in labor, as well as reducing the duration of the active first stage of labor and the total length of labor.